Partisipasi Politik Masyarakat dalam Agenda Pemilihan Gubernur Papua Tahun 2018 - Setia Putra, Imam Radianto Anwar; Kasimat, William Socrates; Purwadi (Jurnal Bina Praja, 2020)
This research article aims to describe communities' participation through direct elections, citizen agreement, and the mandate of representatives with actor interaction in the 2018 Papua gubernatorial election. The regional heads who elected democratically manifest the implementation of direct elections mandated by Acts of 1945 with community participation. The participation of communities in gubernatorial elections comes to the polling places and then casts/elects the desired candidate. More than that, communities' participation explains in-depth the form of involvement and typology of community participation in organizing the Papua Gubernatorial Election. Political participation of Papua communities in terms of political participation related to elections (voting/electing). The research was conducted using a qualitative approach with a case study method to explain the Papua communities' awareness at the Papua gubernatorial election. The data was collected using three methods, namely, the documentation study method, interview method, and Focus Group Discussions (FGD) with respondents from the General Elections Commission (KPU), the Regional Government of Papua Province, the Legislative and the Papuan People's Assembly (MRP), traditional figures, religious figures, academics, and Papua communities. Based on the quantitative calculation of communities participating in the gubernatorial election, it reached 88.44% of the total voters of 3,447,008 people who entered the final voter list, meaning that many communities used their voting rights. There were three mechanisms to facilitate community political participation in the Papua gubernatorial election, including direct mechanisms, citizen agreement, and representative mandates. Increasing the quality of political participation of communities in gubernatorial elections begins with regulations governing the legal norms of gubernatorial elections. It needs adjustment to the paradigm, and various experiences of holding Papua gubernatorial elections have been running to date. The standards that must be considered starting from the system, model, mechanism, and form of involvement of gubernatorial election organizers, so that the absolute and actual political participation of the community is formed.